Factor Xa Inhibitors in the Control of Thrombogenesis - Fareed, J.; Walenga, Jeanine M.; Hoppensteadt, Debra A.; Kaiser, Brigitte; Jeske, W. (Hämostaseologie, 1999)
It is now well recognized that drugs with sole anti-Xa activity are capable of producing antithrombotic effects. The basic and clinical studies with pentasaccharide have validated this hypothesis. Synthetic heparin pentasaccharide is currently undergoing clinical trials in the prophylaxis of DVT in orthopedic surgery. While the naturally occuring direct anti-Xa agents such as antistatin, TAP and Yagin are potent anti-Xa agents their clinical development is delayed due to several unresolved developmental issues. On the other hand, several peptidomi-metic agents also demonstrate varying degrees of oral and subcutaneous bioavailability. One of these agents namely the DX 9065a is in clinical trials at this time. The factor Xa inhibitors exhibit a higher margin of safety in contrast to the antithrombin agents, however, their anticoagulant effects are somewhat weaker than the antithrombin agents. Thus, these agents may prove to be very useful in the prophylactic management of both the thrombotic and cardiovascular disorders. However, their use as an anticoagulant may not be very practical. These agents can be given as adjunct agents with hirudin and related antithrombin agents. These agents may also be of value in the outpatient management of thrombotic disorders. These agents may also be of value as an adjunct to various other antithrombotic drugs. Additional adjunct uses as with the antithrombin drugs, GP llb/llla inhibitors, thrombolytic agents and TFPI may increase the therapeutic index of many of these agents. It should be emphasized that each of these individual anti-Xa agents represent distinct drugs which require individual specific dosage optimization.
Keywords: Factor Xa; Xa inhibitor; thrombogenesis